Study using a CFD approach of the efficiency of a roof ventilation closure system in a multi-tunnel greenhouse for nighttime microclimate optimization (2020)
The thermal efficiency of naturally ventilated greenhouses is limited due to the permanent exchange of air through the vents, especially during the night hours. The objective of the work consisted in evaluating a system of inflatable air ducts that close the roof vents during the night as a strategy to reduce the energy loss during these hours. For the development of this work, we applied the computational fluid dynamics (CFD) method to a passive multi span greenhouse operating under the dominant nocturnal climatic conditions of the Bogota savannah (Colombia). The results indicated that the use of the ducts system reduces the value of the negative thermal gradient between the interior and exterior of the greenhouse. The CFD model used was validated by comparing experimental data and simulated data and by calculating goodness-of-fit parameters, finding that the numerical model predicts satisfactorily and with an adequate degree of fit the actual thermal behavior of the greenhouse evaluated.